Pengaruh Penambahan Aspal Emulsi pada Lapis Pondasi Hasil Daur Ulang dengan Semen (CTRB) terhadap Kinerja Struktural Perkerasan Lentur - Eri Susanto Hariyadi; Mutiara Mahardika (MEDIA KOMUNIKASI TEKNIK SIPIL, 2025)
The scarcity of natural materials that meet specifications for road rehabilitation has encouraged the utilization of recycled pavement materials, particularly cement-treated recycled base (CTRB). Despite its widespread use, CTRB is susceptible to shrinkage cracking, which can lead to reflective cracking in the surface layer and reduce pavement service life. This study investigates the performance of CTRB and a modified mixture incorporating emulsified asphalt—designated as IRBCAE (In-place Recycling with Cement and Asphalt Emulsion)—to mitigate shrinkage-induced cracking. Both mixtures were prepared using recycled aggregates containing 5.34% residual asphalt, with a composition of 49% surface course and 51% base course aggregates. Resilient modulus testing was conducted to evaluate mechanical behavior, and pavement structural responses were analyzed using KENPAVE software. The results indicate that IRBCAE exhibits viscoelastic characteristics with superior fatigue cracking resistance, whereas CTRB demonstrates higher stiffness and greater resistance to permanent deformation. In practical application, CTRB requires a thicker asphalt overlay to prevent reflective cracking, while IRBCAE enables the use of a thinner asphalt layer. The differences in structural performance between the two mixtures provide a basis for selecting suitable stabilization methods for recycled base layers.